CINTA DAN PENGORBANAN DALAM NOVEL KEMBALI KE PELUKAN CINTA KARYA FREDY S: KONSEP CINTA ERICH FROMM - Selvi, Selvi; Nensilianti, Nensilianti; Faisal, Faisal (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2026)
This study aims to reveal the forms of love and sacrifice found in Fredy S.’s novel Kembali ke Pelukan Cinta based on Erich Fromm’s concept of love. This research employs a descriptive qualitative method with a literary psychology approach. The data consist of textual excerpts, sentences, and dialogues in the novel that represent Fromm’s five objects of love: brotherly love, motherly love, erotic love, self-love, and love of God. The results show that the novel portrays love in various dimensions of humanity accompanied by sacrifice as a logical consequence of love itself. Brotherly love appears in the friendships between characters; motherly love is shown through the parents’ care for their children; erotic love is depicted through the relationship between Rosana and Herman; self-love is seen in the characters’ efforts to accept themselves and their past; while love of God emerges from the characters’ religious awareness of divine power. Each form of love is always accompanied by acts of sacrifice—physical, emotional, or spiritual. These findings affirm the relevance of Erich Fromm’s concept of love in understanding the dynamics of love and humanity in literary works